EDUCATIONAL LANDSCAPE OF INDIA: UNRAVELLING GENDER AND REGIONAL DISPARITIES FOR SUSTAINABLE DEVELOPMENT - Upadhyay, Sugeeta (PUPIL: International Journal of Teaching, Education and Learning, 2024)
In the comprehensive assessment of societal well-being, education emerges as a pivotal factor. This study, framing education as a transformative process crucial for enhancing overall societal welfare, zeroes in on examining disparities in the utilization of educational services among diverse social strata. This scrutiny is crucial as it has the potential to perpetuate economic inequities. Key focal points of this study address gender and regional disparities in illiteracy, gross enrolment ratio, and educated unemployment within Indian states. This paper deals with two hypotheses, the first one being that woman from disadvantaged backgrounds in rural areas and states with lower GDP, experience diminished access to education compared to other economic and social segments while the second hypothesis is that economic growth has influenced regional disparities, leading to educational gaps between rural and urban areas, as well as economically advanced and backward regions. Through a meticulous analysis of data encompassing different income groups, genders, fields of education, and regions, this research seeks to elucidate the evolving patterns of educational access. The findings from this study hold significant policy implications. The insights gained are expected to inform the allocation of public resources, with a specific focus on higher education, addressing the educational needs of women and marginalized populations throughout India. In summary, this research contributes substantively to the ongoing discourse surrounding educational reform and equity within the dynamic educational landscape of India.